A novel eddy current testing error compensation technique based on mamdani-type fuzzy coupled differential and absolute probes - Abdalla A.N.; Ali K.; Paw J.K.S.; Rifai D.; Faraj M.A. (MDPI AG, 2023)
Aircraft manufacture; Coatings; Computer circuits; Cracks; Error compensation; Fuzzy logic; Nuclear industry; Probes; Thickness measurement; Compensation techniques; Development designs; Differential probes; Fuzzy logic techniques; General description; Inspection technique; Lift offs; Measurement of defects; Eddy current testing